Knowledge, attitudes, and practices related to antibiotic use in Paschim Bardhaman District: A survey of healthcare providers in West Bengal, India - Nair, Mohit (PLoS One, 2019)
INTRODUCTION: Antibiotic misuse is widespread and contributes to antibiotic resistance, especially in less regulated health systems such as India. Although informal providers are involved with substantial segments of primary healthcare, their level of knowledge, attitudes, and practices is not well documented in the literature. OBJECTIVES: This quantitative study systematically examines the knowledge, attitudes, and practices of informal and formal providers with respect to antibiotic use. METHODS: We surveyed a convenience sample of 384 participants (96 allopathic doctors, 96 nurses, 96 informal providers, and 96 pharmacy shopkeepers) over a period of 8 weeks from December to February using a validated questionnaire developed in Italy. Our team created an equivalent, composite KAP score for each respondent in the survey, which was subsequently compared between providers. We then performed a multivariate logistic regression analysis to estimate the odds of having a low composite score (<80) based on occupation by comparing allopathic doctors (referent category) with all other study participants. The model was adjusted for age (included as a continuous variable) and gender. RESULTS: Doctors scored highest in questions assessing knowledge (77.3%) and attitudes (87.3%), but performed poorly in practices (67.6%). Many doctors knew that antibiotics were not indicated for viral infections, but over 87% (n = 82) reported prescribing them in this situation. Nurses, pharmacy shopkeepers, and informal providers were more likely to perform poorly on the survey compared to allopathic doctors (OR: 10.4, 95% CI 5.4, 20.0, p<0.01). 30.8% (n = 118) of all providers relied on pharmaceutical company representatives as a major source of information about antibiotics. CONCLUSIONS: Our findings indicate poor knowledge and awareness of antibiotic use and functions among informal health providers, and dissonance between knowledge and practices among allopathic doctors. The nexus between allopathic doctors, pharmaceutical company representatives, and informal health providers present promising avenues for future research and intervention.